(untitled) (Research, Society and Development, 2021)
Pediatric obesity, when left untreated, tends to generate several complications that can extend into adulthood. Proper management allows good results, providing better quality of life to patients. In this context, the objective of this study was to investigate the main nutritional and pharmacological therapies used in this condition. A systematic review of the literature was carried out, based on the search for scientific articles indexed in PubMed, ScienceDirect and Scielo, using the following descriptors: pediatric obesity, treatment, sibutramine, orlistate, liraglutide and breastfeeding, as well as their translations into English. Healthy eating habits, associated with the practice of physical exercises, are considered effective treatment strategies, even for cases of severe obesity, and well-structured nutritional monitoring is indispensable for therapeutic success. Anti-obesity drugs, on the other hand, are resources used when changes in lifestyle alone are not sufficient to achieve satisfactory results. According to the Brazilian Society of Pediatrics, the most recommended pharmacotherapeutic possibilities are sibutramine, orlistat and liraglutide. However, these agents, despite triggering beneficial effects, can generate adverse events, requiring the constant monitoring of patients. Thus, it is extremely important that the prescriber makes a rigorous assessment of the risks and benefits provided by the available anti-obesity pharmacotherapy, in addition to beneficial activities developed by the multidisciplinary health team for the improvement of the child’s habits, aiming at maintaining long-term results.